2020
DOI: 10.1136/gutjnl-2019-319227
|View full text |Cite
|
Sign up to set email alerts
|

TREM-2 defends the liver against hepatocellular carcinoma through multifactorial protective mechanisms

Abstract: ObjectiveHepatocellular carcinoma (HCC) is a prevalent and aggressive cancer usually arising on a background of chronic liver injury involving inflammatory and hepatic regenerative processes. The triggering receptor expressed on myeloid cells 2 (TREM-2) is predominantly expressed in hepatic non-parenchymal cells and inhibits Toll-like receptor signalling, protecting the liver from various hepatotoxic injuries, yet its role in liver cancer is poorly defined. Here, we investigated the impact of TREM-2 on liver r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 72 publications
5
60
0
Order By: Relevance
“…On the contrary, high TREM2 expression levels were significantly associated with tumor type, higher T stage, higher TNM stage, and higher GRADE in LIHC. It has been described in articles that TREM2 is a new type of tumor suppressor gene for liver cancer, and the decreased expression of TREM2 in HCC patients is associated with poor prognosis [25] .the results are consistent. We conclude that high TREM2 expression may can as an independent prognostic factor for KIRP and liver patients.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…On the contrary, high TREM2 expression levels were significantly associated with tumor type, higher T stage, higher TNM stage, and higher GRADE in LIHC. It has been described in articles that TREM2 is a new type of tumor suppressor gene for liver cancer, and the decreased expression of TREM2 in HCC patients is associated with poor prognosis [25] .the results are consistent. We conclude that high TREM2 expression may can as an independent prognostic factor for KIRP and liver patients.…”
Section: Discussionsupporting
confidence: 52%
“…TREM2 has been confirmed as a marker for tumor-associated macrophages (TAMs) and monocytes [22]. [25] .the results are consistent. We conclude that high TREM2 expression may can as an independent prognostic factor for KIRP and liver patients.…”
Section: Discussionmentioning
confidence: 59%
“…This work revealed that Trem-2 controls the replenishment of liver macrophage populations after acute and chronic hepatotoxic damage and is a critical determinant of swift tissue repair responses conditioning the emergence of endothelial lineage cells during regeneration. Recent reports proposed that lack of Trem-2 expression in non-parenchymal cells contributes to increased fibrosis in Trem-2 KO mice submitted to CCl4 treatment, to increased liver inflammation after acute APAP treatment ( 24 ) and to increased susceptibility to hepatocarcinogenesis ( 33 ). We noted that Trem-2 KO mice did not show significantly higher intensity of liver damage during acute injury (APAP-D1) but showed sustained tissue damage throughout the tissue repair phase (APAP-D3).…”
Section: Discussionmentioning
confidence: 99%
“…Another study supports the protective role of TREM2 in hepatocarcinogenesis. TREM2 attenuates inflammation, oxidative stress and Wnt ligand secretion, preventing hepatocyte proliferation and damage [21]. The differing functions of TREM2 in vivo and in vitro may be caused by differences in animals and cell lines [123].…”
Section: Roles Of Trem In Liver Tumorigenesismentioning
confidence: 99%